The 1st pull in weightlifting movements - Favre, M. W. (coachesinfo.com, 2008)
Explanation of the importance, technique and the way of execution of the 1st pull in the clean and the snatch, which occurs from the moment of separation (MOS) of the bar from the floor to where it reaches the area of the knees. The importance for executing the1st Pull correctly is: - It gets the bar moving without expending too much energy. - It establishes and maintains an optimal combined center of gravity (COG). - Precedes and can potentiate the "Scoop" or "Double-knee Bend" phase which in turn sets up the 2nd pull The 1st Pull is where "big" lifts are made or lost. Some common technical errors during the 1st pull are: - Lifter does not remove slack from the bar. - Lifter jerks bar off the floor. - The lifter must ease the bar off the floor rather than "rip" it up. - Smooth and controlled are the keys to success. - Lifter bends arms. - Lifter rolls onto balls of feet or toes - Weight has pulled lifter forward rather than lifter pulling weight backward. - Lifter allows shoulders to fall and back to bend. - All of which will result in poor, or no transition phase from 1st to 2nd Pull. Thus negatively affecting the 2nd Pull.